Pemberdayaan UMKM Melalui Program Bestee Dalam Upaya Meningkatkan Daya Saing Bisnis di BTPN Syariah MMS Rambipuji Kabupaten Jember - Rachman, Jalaluddin Abdul; Nisa, Fauzatul Laily; Utami, Anisa Fitria (Jurnal Pengabdian UNDIKMA, 2024)
Community service through the Bestee program assistance aims to increase the competitiveness of customers who are Micro, Small, and Medium Enterprises (MSMEs) MMS Rambipuji. Through various forms of structured and sustainable mentoring, this program focuses on providing the necessary knowledge, skills, and human resource training for MSME actors in optimizing and developing their business activities. So that it can improve the standard of living and economy of MSME customers. The method of implementing this service uses socialization of Bestee programs, training, and mentoring. The evaluation instrument of this activity uses a questionnaire and is analyzed descriptively. The results of this service show that the mentoring of this Bestee program has a significant impact on changing the thinking and strategies of MSME actors. This mentoring includes improving marketing strategies, business identity, and good management, including financial management, human resources, and business operations. Focusing on improving understanding of proper management and strategies as well as modern marketing can help MSME actors reach a wider range of consumers and increase sales.